2005
DOI: 10.14310/horm.2002.11143
|View full text |Cite
|
Sign up to set email alerts
|

Improved somatic growth following adenoidectomy and tonsillectomy in young children. Possible pathogenetic mechanisms

Abstract: The effect of Adenotonsillectomy on somatic growth was studied prospectively in 57, randomly selected children (31 boys, 26 girls), aged 5.03+/-1.32 (mean+/-1SD) years. The indication for surgery was adenotonsillar hypertrophy with or without recurrent infections. Weight, height, triceps skinfold thickness, and Body Mass Index were measured prior to the operation and 6-13 months afterwards. Weight was significantly improved following T&A in all children. The improvement in height was significantly only for chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 41 publications
(32 reference statements)
0
23
0
2
Order By: Relevance
“…Significant increases in height z scores after adenotonsillectomy for pediatric OSAS have been reported in many studies, 3,11,14,16,18 but not others. 9,12 Our results demonstrated no significant differences between the eAT and WWSC groups with regard to postoperative height, although in the eAT group there was a significant increase in the height z score after 7 months.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Significant increases in height z scores after adenotonsillectomy for pediatric OSAS have been reported in many studies, 3,11,14,16,18 but not others. 9,12 Our results demonstrated no significant differences between the eAT and WWSC groups with regard to postoperative height, although in the eAT group there was a significant increase in the height z score after 7 months.…”
Section: Discussionmentioning
confidence: 92%
“…[1][2][3][4][5] Adenotonsillar hypertrophy is the primary cause of OSAS in children, and is usually treated with adenotonsillectomy (AT). AT has been reported to accelerate weight [6][7][8][9][10][11][12][13][14] in children with baseline failure to thrive (FTT), 1,3,4,15 normal weight patients, 9,11,14,[16][17][18][19][20] obese individuals, 9,13,16,21,22 and infants. 10 The majority of studies also have demonstrated an increase in the height growth rate after AT for OSAS, 3,6,11,17,23,24 but other studies reported no significant differences.…”
Section: (Continued On Last Page)mentioning
confidence: 99%
“…In the study performed by Vontetsianos (34) in which the follow-up period after adenotonsillectomy was 6-13 months, weight SDS values and height SDS values (especially in children younger than 5 years of age) were found to be significantly increased after operation.…”
Section: Discussionmentioning
confidence: 95%
“…Excessive obstruction and presence of additional problems including laryngomalacia and Down syndrome increase this rate (33,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…GH is released in a pulsatile fashion over a 24-h period, with the highest GH values being associated with the onset of slow-wave sleep. It has been shown that a reduced amount of slow-wave sleep occurs in children with adenoid hypertrophy and that this results in a decrease in sleep-associated GH secretion (22). Other studies, however, found larger mandibular widths and larger mandibular arch lengths in adenoid subjects (5).…”
Section: Discussionmentioning
confidence: 99%